Solid state engineering physics - Basu, Prabir K. (CRC Press, 2009)
This text first deals with the crystal structure of new materials, discussing point defects both qualitatively and quantitatively. Focusing on quantum physics, the next chapter examines the dual nature of particles and the Schrodinger equation. The authors then cover the free electron theory of metals and semiconductors. They also study the details of photoconductors and photovoltaic cells as well as the magnetization factor for various magnetic materials, which offers an understanding of the controlling parameter responsible for the origin of magnetization within the material. The final chapter focuses on the exciting phenomenon of superconductivity.